Investigation of Helicobacter pylori antigen in stool samples of patients with upper gastrointestinal complaints - Calik,Zeki (2016)
Abstract Helicobacter pylori infection is usually acquired in early childhood and it can persist throughout life without antibiotic treatment. This study aimed to compare the accuracy of the noninvasive H. pylori Stool Antigen Test-applied on the stool samples with the invasive gold standart Rapid Urease Test-applied on the gastric biopy samples of patients with upper gastrointestinal complaints. After endoscopy, biopsy and stool specimens were taken in 122 patients. The infection was detected with rapid urease test which is accepted as gold standart test. Rapid, one-step H. pylori card test was applied to all patients stool specimens. In this study 106 of the 122 patients (86.8%) were positive for H. pylori infection, while 16 of the 122 patients (13.2%) were negative. H. pylori card test was negative in 13 of the 16 patients and was positive in 98 of the 106. The sensitivity, specifity, positive and negative predictive values were 92.45%, 81.25%, 97.02%, and 61.90%, respectively. H. pylori card test is rapid, easy, noninvasive and inexpensive methods for detection H. pylori infection. This test showed high sensitivity and specificity. Additionally, it may be a good alternative to invasive tests for the detection of H. pylori infections especially in children.